Impact of Influencer Marketing on Small and Medium Enterprises in Kenya - Muchori, Margaret Muthoni; Reid, Patrick (Journal of Marketing Studies, 2026)
Purpose: Influencers in social media have developed into a powerful marketing force, significantly impacting Kenyan small and medium-sized enterprises (SMEs). By leveraging the expansion of social media sites such as Instagram, TikTok, and Facebook, influencers have transformed how businesses engage with clients. Through their large numbers of followers and credibility, influencers help SMEs increase brand visibility, gain new customers, and boost sales. This emerging form of marketing is particularly beneficial to Kenyan SMEs, in that it offers a low-cost alternative to traditional advertising and enables direct interaction with targeted groups. Consequently, social media influencers' power is reshaping the business landscape, opening up possibilities for expansion for SMEs in an increasingly digitalized economy. This study aims to assess the impact of influencer marketing on SMEs in Kenya. Methodology: This study adopted positivism philosophy which is based on data collection. The study used mixed approach research design. The study collected 385 questionnaires .The study used primary data. Data was processed and analysed with the help of statistical techniques such as descriptive statistics and inferential analysis for quantitative data and thematic analysis for qualitative responses. Findings: The findings confirm that social media engagement is a key driver of business success for SMEs in Kenya, as engaging with customers helps build brand trust, increases visibility, and drive sales. The study confirms that social media comments are a significant component of SME product design and marketing planning in Kenya. SMEs have customer-driven improvement, more sophisticated marketing tactics, and better customer interactions. The study concluded that there is proof that influencer marketing plays an important role in SMEs in Kenya. Unique Contribution to Theory, Practice and Policy: Nevertheless, companies experience challenges in selecting influencers and measuring ROI. SMEs must adopt specialized social media management strategies to increase engagement, ensuring frequent and effective online presence. Personalized responses to customers' inquiries can help to create stronger relationships and to build brand loyalty by making customers feel listened to and valued. In addition, companies must prioritize creating visually engaging content, as captivating visuals can significantly increase interactions and translate into higher sales conversions. By implementing these steps, SMEs can maximize the success of their social media efforts and improve overall brand performance.